Firefly algorithm with adaptive control parameters - Wang, Hui; Zhou, Xinyu; Sun, Hui; Yu, Xiang; Zhao, Jia; Zhang, Hai; Cui, Laizhong (Soft computing (Berlin, Germany), 2017)
Firefly algorithm (FA) is a new swarm intelligence optimization method, which has shown good search abilities on many optimization problems. However, the performance of FA highly depends on its control parameters. In this paper, we investigate the control parameters of FA, and propose a modified FA called FA with adaptive control parameters (ApFA). To verify the performance of ApFA, experiments are conducted on a set of well-known benchmark problems. Results show that the ApFA outperforms the standard FA and five other recently proposed FA variants.